The future of private sector unions in the United States: part I. (Journal of Labor Research)
A special issue on the future of private sector unions in the U.S. is presented. Topics discussed include the future of private sector unionism in the U.S.; twilight for organized labor; labor unions as victims of their political success; information technology, unions, and the new organizations; the fall and future of unionism in construction; a European perspective on American labor; changes in the U.S. environment and declining private sector unionism; and human resource management practices and worker desires for union representations.